1999
DOI: 10.1093/tropej/45.6.327
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and provoked growth hormone (GH) secretion and insulin-like growth factor I (IFG-I) concentration in patients with beta thalassaemia and delayed growth

Abstract: Growth retardation in children with thalassaemia major is multifactorial. We studied the growth hormone (GH) response to provocation by clonidine and glucagon, measured the circulating concentrations of insulin, insulin-like growth factor-I (IGF-I), IGF-binding protein-3 (IGFBP3), and ferritin, and evaluated the spontaneous nocturnal (12 h) GH secretion in prepubertal patients with thalassaemia and age-matched children with constitutional short stature (CSS) (height SDS < -2, but normal GH response to provocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
4
16
0
3
Order By: Relevance
“…For GH, we found a strong positive correlation between peak responses during ITT and GST, which was comparable to the results of Spathis et al (21). Soliman et al concluded previously that glucagon was at least as good as the ITT in stimulating GH release (27). Moreover, Aimaretti et al found that although the ITT was a more effective stimulus than L-arginine, L-dopa, and clonidine, glucagon was the strongest stimulus after ITT (28).…”
Section: Discussionsupporting
confidence: 90%
“…For GH, we found a strong positive correlation between peak responses during ITT and GST, which was comparable to the results of Spathis et al (21). Soliman et al concluded previously that glucagon was at least as good as the ITT in stimulating GH release (27). Moreover, Aimaretti et al found that although the ITT was a more effective stimulus than L-arginine, L-dopa, and clonidine, glucagon was the strongest stimulus after ITT (28).…”
Section: Discussionsupporting
confidence: 90%
“…Serum parameters of group 2 of patients with BTM, in our study were insignificantly different from their control group 4 except as regard serum ferritin; this ferritin was accused in several studies before to be the cause of short stature and decreased their serum levels of IGF-1 and its binding protein IGFBP-3. 16 In our study there was no correlation between serum ferritin and any other variable of the patients with BTM, the result which agreed with that of Karydis et al 2004 21 and that of Vedergor et al 2007, 22 who found no significant correlation between serum ferritin and the peak levels of GH or IGF1. In our study there was a statistically significant correlation between T4 and upper/lower segment ratio, this result could be explained by the known effect of thyroid hormone on the body proportions.…”
supporting
confidence: 90%
“…IGFBP3 in our study was also statistically significantly lower than in the control group p<0.05, the result which agreed with that of Chrysis et al 2001 13 who found low levels of IGF1 and IGFBP3 in their thalassemia patients with short stature and decelerated growth compared to those with normal growth. Not all of our thalassemia patients were with retarded linear growth, 57.6 % were below the 5th percentile for age and sex (BTM group1), the mean age of them was higher than the rest of the group (BTM group 2), Soliman et al 1999 16 reported that after the age of four, there is significant growth retardation involved short stature and sitting height. This age difference between the two thalassemia groups in our study, may explain the insignificant difference between the two groups as regard serum levels of IGF1 and IGFBP3, as IGF1 and IGFBP3 are known to increase slowly with age in childhood, reaching a peak level at puberty and decrease thereafter.…”
Section: Discussionmentioning
confidence: 79%
“…Conflicting results have been reported with respect to pituitary secretion of GH and its regulation from the hypothalamus 14 " 22 . Conflicting results have been reported with respect to pituitary secretion of GH and its regulation from the hypothalamus 14 " 22 .…”
mentioning
confidence: 99%